2016
DOI: 10.4049/jimmunol.1601054
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of IFN-Inducible and Damage-Response Pathways in Chronic Graft-versus-Host Disease

Abstract: Although Chronic Graft-versus-Host Disease (CGVHD) is the primary non-relapse complication of allogeneic transplantation, understanding of its pathogenesis is limited. To identify the main operant pathways across the spectrum of CGVHD, we analyzed gene expression in circulating monocytes, chosen as in situ systemic reporter cells. Microarrays identified two interrelated pathways: (1) Interferon-inducible genes and (2) innate receptors for cellular damage. Corroborating these with multiplex RNA quantitation, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 64 publications
(85 reference statements)
0
58
0
1
Order By: Relevance
“…However, in clinical alloSCT, in which pharmacologic immunosuppression is given, such a rise in IFN-γ may only infrequently occur, and this may in part contribute to the more global GVL resistance of myeloblastic leukemias. Chronic GVHD (cGVHD) has been associated with a lower risk for AML relapse, and recent data suggest that cGVHD is associated with the action of IFN-γ (37). Perhaps the sustained IFN-γ associated with cGVHD contributes to GVL, along with alloreactive cytolytic T cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical alloSCT, in which pharmacologic immunosuppression is given, such a rise in IFN-γ may only infrequently occur, and this may in part contribute to the more global GVL resistance of myeloblastic leukemias. Chronic GVHD (cGVHD) has been associated with a lower risk for AML relapse, and recent data suggest that cGVHD is associated with the action of IFN-γ (37). Perhaps the sustained IFN-γ associated with cGVHD contributes to GVL, along with alloreactive cytolytic T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-33 receptor, ST2/IL1RL1, now recognized as a biomarker for both acute and chronic GVHD, is also released in response to cell damage (8387). Third, gene expression in circulating monocytes from clinical samples has revealed that multiple interferon (IFN)-inducible genes and receptors for pathogen-associated molecular patterns and damage-associated molecular patterns [known as pattern recognition receptors (PRRs)] become upregulated at the time of onset of chronic GVHD, remaining elevated in patients with active disease (88). These IFN-inducible and PRR genes were comparably upregulated in patients with cutaneous lichenoid infiltrates and in those with extensive sclerotic involvement, providing a common operant mechanism across the spectrum of chronic GVHD manifestations (88).…”
Section: A Three Phase Model For Chronic Gvhd Biologymentioning
confidence: 99%
“…Third, gene expression in circulating monocytes from clinical samples has revealed that multiple interferon (IFN)-inducible genes and receptors for pathogen-associated molecular patterns and damage-associated molecular patterns [known as pattern recognition receptors (PRRs)] become upregulated at the time of onset of chronic GVHD, remaining elevated in patients with active disease (88). These IFN-inducible and PRR genes were comparably upregulated in patients with cutaneous lichenoid infiltrates and in those with extensive sclerotic involvement, providing a common operant mechanism across the spectrum of chronic GVHD manifestations (88). Use of a neutralizing Type I IFN receptor (IFNAR) antibody prevented skin and vascular changes in a sclerotic chronic GVHD murine model (B10.D2→BALB/c), and a similar strategy reduced Th1 activation and collagen production in a phase I clinical trial for patients with for systemic sclerosis (89, 90).…”
Section: A Three Phase Model For Chronic Gvhd Biologymentioning
confidence: 99%
“…In one of the studies, CXCL10 and another CXCR3-binding protein, CXCL9, were both increased. However, only CXCL10 had an ROC curve AUC of ≥0.75, and was validated in different groups [41,42,46]. Another CXCR3 ligand involved in the pathogenesis of cGVHD is CXCL11.…”
Section: Useful Cgvhd Biomarkersmentioning
confidence: 99%